Modernisasi UMKM Mie Ayam Mas Nok Melalui Pemanfaatan Media Sosial Dan Pembuatan Logo - Santi Rimadias; Nikita Dewi Anjani Sudrajat; Zaid Muhammad Zaidan (Pusat Riset dan Inovasi Nasional, 2024)
Micro, Small and Medium Enterprises (MSMEs) need to compete effectively in the market in terms of increased capacity to adapt to the dynamic business environment. MSMEs need to respond promptly to evolving market trends, technological advances, and changing consumer preferences. However, not all MSMEs have made the necessary adaptations in order to thrive in a dynamic business environment. This community service focuses on Mie Ayam Mas Nok, an MSME that faces specific challenges, especially the lack of social media utilization and the absence of a distinctive business logo. To overcome these problems, community service activities were carried out by providing targeted assistance to MSMEs Mie Ayam Mas Nok. This service activity aims to empower them through effective utilization of social media platforms and the creation of unique business logos, thereby increasing their competitiveness in a dynamic business environment. Using a combination of observation, interviews, and surveys, this community service initiative yielded positive results. MSMEs Mie Ayam Mas Nok successfully integrated social media into their business strategy and obtained a distinctive business logo. These improvements have significantly increased the competitiveness of their businesses, equipping them to thrive in an ever-changing and competitive business environment.